(2x+3)(3x+7)=0

Simple and best practice solution for (2x+3)(3x+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+3)(3x+7)=0 equation:


Simplifying
(2x + 3)(3x + 7) = 0

Reorder the terms:
(3 + 2x)(3x + 7) = 0

Reorder the terms:
(3 + 2x)(7 + 3x) = 0

Multiply (3 + 2x) * (7 + 3x)
(3(7 + 3x) + 2x * (7 + 3x)) = 0
((7 * 3 + 3x * 3) + 2x * (7 + 3x)) = 0
((21 + 9x) + 2x * (7 + 3x)) = 0
(21 + 9x + (7 * 2x + 3x * 2x)) = 0
(21 + 9x + (14x + 6x2)) = 0

Combine like terms: 9x + 14x = 23x
(21 + 23x + 6x2) = 0

Solving
21 + 23x + 6x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(7 + 3x)(3 + 2x) = 0

Subproblem 1

Set the factor '(7 + 3x)' equal to zero and attempt to solve: Simplifying 7 + 3x = 0 Solving 7 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 0 + -7 3x = 0 + -7 Combine like terms: 0 + -7 = -7 3x = -7 Divide each side by '3'. x = -2.333333333 Simplifying x = -2.333333333

Subproblem 2

Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5

Solution

x = {-2.333333333, -1.5}

See similar equations:

| 7x-13=2x-3 | | y=4x+160 | | 12x+10y=202 | | 3x+20=8-x | | -80=4x-16+4 | | 5/6p=20 | | f/-7-8=2 | | 11x-7=5x-13 | | 5z+5=2(8z-3) | | 22-3x=4x | | 4y-4=7(y-1) | | x(x-0.05)=300 | | -10+4w+6=-2w+23-3w | | 1b+2=-3b | | -10+4w+6=-23-3w | | 12/8x=7/10 | | 7a-4=4a+19 | | 9x^4-8x^2= | | 3x-11/4=-2x | | 3(5b-2)+2=26 | | 8a+3a+18=8+7a+6 | | 4=5/w-2 | | -1/9x=-3/4 | | -1=-3z+20 | | [x-3]=4x+9 | | 3(y-8)-2y=12 | | -9=r+(-2) | | 5.2/4.4 | | -4(d+12)=16 | | [-5x]=35 | | -18=3X-3 | | -29=15+y |

Equations solver categories